Occupational heavy lifting and risk of ischemic heart disease and all-cause mortality - Petersen Christina B; Eriksen Louise; Tolstrup Janne S; Søgaard Karen; Grønbæk Morten; Holtermann Andreas (BMC, 2012)
Abstract Background Occupational heavy lifting is known to impose a high cardiovascular strain, but the risk of ischemic heart disease (IHD) from occupational heavy lifting is unknown. The objective was to investigate the association between occupational heavy lifting and risk of IHD and all-cause mortality, and the influence of occupational and leisure time physical activity on this association. Methods Data were analyzed from 1987, 1994, and 2000 from the Danish National Health Interview Surveys providing a sample of 6,692 working men and 5,921 working women aged 16-85 years without cardiovascular disease at baseline. Conventional risk factors for the outcomes IHD and all-cause mortality were controlled for in Cox analyses. Results Among men, heavy lifting was associated with increased risk for IHD (hazard ratio (HR): 1.52, 95% Confidence interval (95% CI): 1.15, 2.02), while a decreased risk was associated with occupational (HR: 0.50, 95% CI: 0.37, 0.68) and leisure time (HR: 0.73, 95% CI: 0.56, 0.95) physical activity. Referencing men with high occupational physical activity and no heavy lifting, men with high occupational physical activity and heavy lifting did not have an increased risk (HR: 1.11, 95% CI:0.68, 1.82), while men with low occupational physical activity and heavy lifting had a substantial increased risk (HR: 2.56, 95% CI:1.52, 4.32). No significant associations were found for all-cause mortality or for females. Conclusion These findings indicate an excessive risk for IHD from occupational heavy lifting among men, particularly among those with low occupational and leisure time physical activity.